PENGARUH KEPEMIMPINAN DAN JOB DESCRIPTION TERHADAP KEPUASAN KERJA KARYAWAN HOTEL GRASIA SEMARANG (Students' Journal of Economic and Management, 2014)
The existence of a leader and in the organization where the job description is needed to bring the organization to its intended purpose. Both of these can lead to satisfaction or dissatisfaction in the work if not applied properly. Therefore, this study was conducted to determine the effect of leadership on job satisfaction, job description influence on job satisfaction, and the influence of leadership and job description on job satisfaction. This study was conducted at 72 permanent employees Grasia Semarang hotel employee who has worked for at least 2 years, and have minimum education D3. Data collection methods digunaka nberasal of questionnaires. Data analysis methods used include test validity using factor analysis techniques, test reliability with Cronbach Alpha method, the classical assumption test, and multiple linear regression. The results showed an effect partially leadership Leadership significant effect on the improvement of job satisfaction karyawanHotel Grasia Semarang, the job description also affect job satisfaction Grasia Semarang Hotels, and is the dominant variable effect on employee job satisfaction, and leadership simultaneously and job description simultaneously significant effect on employee job satisfaction Grasia Hotel Semarang. The second major contribution of this variable to increased employee satisfaction is at 89.0%. From the results of this study concluded that the better the leadership, and the better the job description, the higher employee satisfaction.Keywords: employee satisfaction, leadership, and job description.